Rediscovery and lectotypification of Rohdea wattii (C.B.Clarke) Yamashita & M.N.Tamura (Asparagaceae) from Manipur, India - Dhatchanamoorthy, Narayanasamy; Devanathan, Krishnamoorthy; Lokho, Kreni; Begum, Syeda Noorunnisa; Balachandran, Natesan (Phytotaxa, 2024)
Rohdea wattii (C.B. Clarke) Yamashita & M.N. Tamura is a subtropical Asiatic species rediscovered after the type collection with a gap of 137 years from Manipur, India. Detailed taxonomic description, color plate, ecology, and nomenclature notes have been provided for this potential economically valuable wild ornamental species. Lectotype for the name R. wattii (≡Campylandra wattii C.B. Clarke) is designated here.